Provenances, preponderances, and distribution of humic acids and organic pollutants in hydro-geosphere: The co-existence, interaction and isotopic biomarkers in the riverine ecosystem. (1st July 2022) - Varma, Kriti; Jha, Pawan Kumar; Mukherjee, Santanu; Singhal, Anjali; Kumar, Manish
Abstract: This paper aims to critically review the importance of geochemical fingerprinting and tracing using biomarkers and stable isotopes in the riverine ecosystem and depicts that isotopic ratios of δ 13 C, δ 15 N, and δ 34 S can be used for tracing pollution sources. Stable isotopes like carbon, hydrogen, nitrogen, oxygen, and sulfur are being used for this purpose, and their isotopic signatures are primarily used to distinguish close sources of organic matter through dual isotopes. The present review is articulated to bridge the critical research gaps of the previous and contemporary documented literature on the genesis and transport of OM between freshwater and marine systems. This review comprehensively provides methods and techniques in geochemical tracing and discusses the future directions to address the challenges of the current methods to enhance the knowledge about the source identification of organic matter in the riverine environment. Tracer geochemistry emphasizes the implications of elemental abundances and isotope ratio variations in geologic substances to track natural earth processes, anthropogenic contaminants, and geochemical signatures in the hydrologic system. The principal constituent of organic matter comprises humic substances like humic acid, fulvic acid, and humin, and these comprise 50–75% of the sediments and DOC in natural waters. Their structural and functional characterization is required to elucidate the transport and fate of organic matter, which are often influenced by several paleoenvironmental factors. Graphical abstract: Image 1 Highlights: Humic substances constitute 50–75% of the sediments and DOC in natural waters. Isotopic ratios of δ 13 C, δ 15 N, and δ 34 S can be used for tracing pollution sources. FT-ICR-MS-ESI is one of the most advanced instruments for ionized organic compounds. The stable isotope values and C/N ratio are influenced by paleoenvironmental factors. δ 88 / 86 Sr can be used as a significant tracer for chemical weathering and pedogenesis.